DIAGNOSTICS OF THE CONDITION OF ELEMENTS OF ELECTRIC POWER SUPPLY SUBSTATION - Toirov, Olimjon; Amirov, Sulton; Khalikov, Sarvar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The article examines the issues of diagnostics of the state of elements of the power supply substation. It is shown that the development of a diagnostic system for the technical condition of electrical equipment of a power supply substation requires the availability of technical means for measuring and monitoring the current state of the substation elements, the availability of computing equipment and should be implemented at a specific operating power supply substation. It is indicated that diagnostics of the main equipment of the power supply substation involves prompt detection of faults as a result of processing the readings of the sensors of the standard control system, readings of the sensors, the standard control system, sensor readings entered manually once a day, monthly and special test data and, taking into account, the problem of diagnosing electrical equipment of a power supply substation is considered. The diagram of the algorithms for diagnosing the state of electrical equipment of a power supply substation and the input parameters for diagnosing the state of a power supply substation are given. An algorithm for assessing the state of a power transformer based on the temperatures of the cooling oil and water, as well as an algorithm for assessing the state of a power transformer based on the temperatures of the winding and core, have been developed. The implementation of the developed diagnostic algorithms allows not only to increase the reliability of equipment operation and reduce the number of serious accidents, but also to provide the station personnel with retrospective technological information for the analysis and planning of equipment operation, its repair and increased efficiency.